2012
DOI: 10.1111/j.1447-0756.2012.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative differentiation between tumor‐related ovarian torsion and rupture of ovarian cyst preoperatively diagnosed as benign: A retrospective study

Abstract: In this study, the patients with ruptured ovarian cyst had elevated CRP levels. Another study has demonstrated that there was risk for necrosis in torsion patients with elevated CRP levels who presented more than 10h after the onset of acute abdomen. Therefore, preoperative differential diagnosis between ovarian torsion and rupture may be possible by combining the findings from preoperative imaging, data on the time from onset of acute abdomen, and CRP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Conversely, cyst rupture rate during adnexectomy is comparable between laparoscopy and laparotomy for tumor < 10 cm; however, for tumors 10 cm laparoscopy was reported to have a significantly higher cyst rupture rate than laparotomy. 3 In our hospital, although we try our best to avoid cyst rupture, it cannot always be circumvented because of individual case characteristics. All malignant tumors in this study were < 10 cm and the mean largest diameter was significantly larger than that of the benign masses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, cyst rupture rate during adnexectomy is comparable between laparoscopy and laparotomy for tumor < 10 cm; however, for tumors 10 cm laparoscopy was reported to have a significantly higher cyst rupture rate than laparotomy. 3 In our hospital, although we try our best to avoid cyst rupture, it cannot always be circumvented because of individual case characteristics. All malignant tumors in this study were < 10 cm and the mean largest diameter was significantly larger than that of the benign masses.…”
Section: Discussionmentioning
confidence: 98%
“…Laparoscopic surgery is more likely to cause cyst rupture than open surgery. 3 These malignant cases essentially undergo a standard laparotomy; however, at present there is no referential data regarding either the prognosis or the consensus to indicate laparoscopy unconditionally for early-stage ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although some multimodal imaging techniques can be used to diagnose OT, an accurate diagnosis is difficult due to the nonspecific findings and the long list of differential diagnoses. Ruptured ovarian cysts should be considered first in the differential diagnosis because patients with ruptured ovarian cysts present with acute abdominal signs, with some resemblance to OT, and are difficult to clearly differentiate preoperatively [ 5 ]. All participants in this study underwent conventional USG and Doppler USG examinations, while CT was only performed for a patient with a huge abdominopelvic mass in order to exclude other differential diagnoses, such as a ruptured ovarian cyst.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that conservative surgery alone was insufficient to preserve ovarian function. Because a prolonged duration of torsion may lead to a loss in ovarian function, an early diagnosis is important to protect the ovary from ischemia and necrosis [ 5 ]. Daponte et al [ 6 ] demonstrated that increases in certain inflammatory markers in the serum, such as IL-6, can play an important role in the early diagnosis of patients with adnexal torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation